GOVERNMENT POLICY IN PREVENTION OF HUMAN TRAFFICKING IN WEST LOMBOK REGENCY NUSA TENGGARA BARAT - Idul Adnan Rasim (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2022)
Based on data from the Crisis Centre belonging to the National Agency for the Placement and Protection of Indonesian Migrant Workers which is called BNP2TKI, there were 1,759 complaints from workers assigned abroad as of/January-March 2019, where 71 cases were confirmed as human trafficking. and 2,430 cases which have indicators of human trafficking and there are 32 cases of trafficking in persons from the province of Nusa Tenggara Barat where as many as 59 victims are from West Lombok Regency. Using normative empirical research or also best known as field research, this paper applied the descriptive analysis method in analysing the data and found the following: forms and models of human trafficking in West Lombok Regency, Nusa Tenggara Barat done by a scalper who approached potential target induvidually ( home-to-home / door-to-door), then offered a job with a big number of salary to the victim, using nonprocedural ways, document falsification and persuading victims to escape from legal corporate. The duties of the West Lombok government are to prevent the occurrence of the criminal act of human trafficking there for socialization in the community and schools in West Lombok about procedurally being legal workers migrants and law enforcement on the criminal offender are crucial to be born in mind.